A atuação das Relações Públicas no Marketing Político - Silva, Diuliane Mayara da [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
This paper discusses the performance of pubic relations professional in the field of political marketing, using its tools and strategies in accordance with the established goals. The study presents a general approach to marketing, its origin, tools, strategies, starting for the main types of marketing. In the end, we discuss the relationship between political marketing and public relations. Public relations trace a new path and a new opportunity for performance across the political marketing, and the chances for working at election time, at an earlier stage and later, the politician should think about maintaining their image as well as a way to generates credibility in an upcoming campaign

Este trabalho debate a atuação do profissional de relações púbicas na área de marketing político, utilizando suas ferramentas e estratégias de acordo com os objetivos estabelecidos. O trabalho apresenta uma abordagem sobre marketing geral, sua origem, ferramentas, estratégias, partindo para as principais tipologias de marketing. Ao final, é discutida as relações entre marketing político e as relações públicas. As relações públicas traçam um novo caminho e uma nova oportunidade de atuação através do marketing político, pois além das chances de trabalho na época eleitoral, na fase anterior e posterior, o político deve pensar na manutenção de sua imagem também, como forma de gerar credibilidade para uma próxima campanha
Keywords: Relações publicas; Marketing; Marketing político; Propaganda; Campanha eleitoral; Public relations; Marketing; Political marketing